“WHAT COLOUR IS OUR BLOOD?” EVALUATION OF STUDENTS’ AND PROSPECTIVE TEACHERS’ OPINIONS IN TERMS OF ALTERNATIVE CONCEPTS - Solmaz Aydin BEYTUR,; Sibel Gürbüzoğlu YALMANCI, (MOJES: Malaysian Online Journal of Educational Sciences, 2022)
The main purpose of this study is to identify alternative concepts that students possess on the colour of blood and determine the strength of those concepts as well as the reasons for why students constructed them. The sample of the study consisted of participants who were selected from three different cohorts of students (i.e. middle-school, high-school and university). 233 participants were recruited from two middle-schools, 207 students from two high-schools, and 181 third year pre-service teachers from a public university in Kars, Turkey. The study followed the survey method and the data was collected using the “What colour is our blood?” questionnaire. Content analysis was used to analyse the data collected from the questionnaire which consisted of open-ended questions. Analysis of the data indicated that students possessed various alternative concepts on the colour of blood. Furthermore, results suggested that the numbers of students holding the alternative concept with regards to the colour of blood being blue increases day by day. It was found that information sources such as school, teacher, family, friends, media and various visual elements play a role in the emergence of those alternative concepts.